Functional independence 6 months to 5 years after traumatic brain injury: Opportunities for recreational therapy - Gregory, MBA, CTRS, Donna L.; Hawkins, PhD, LRT/CTRS, Brent L.; Chan, MD, MPH, Leighton (American Journal of Recreation Therapy, 2018)
Traumatic brain injury (TBI) can have a lasting and devastating impact on individuals and their families. The effects of TBI are complex and may impair cognitive and psychosocial function. The purpose of this study was to identify impairments 6 months to 5 years after TBI and to recognize opportunities for recreational therapy (RT) to address functional needs. Results indicated that psychosocial adjustment and cognitive improvements occurred between 90 and 180 days after injury. However, impairment in several cognitive and psychosocial adjustment subscales persisted 1 to 5 years after injury. Community-based RT interventions focused on cognitive compensatory strategies, environmental adaptation, and social skill development may help individuals experiencing long-term impairments.